Hypoxia stimulates neural stem cell proliferation by increasing HIF"‘1Î± expression and activating Wnt/Î²-catenin signaling - Qi, C.; Zhang, J.; Chen, X.; Wan, J.; Wang, J.; Zhang, P.; Liu, Y. (Cellular and Molecular Biology, 2017)
Evidence indicates that after brain injury, neurogenesis is enhanced in regions such as hippocampus, striatum, and cortex. To study the role of hypoxia-inducible factor-1 (HIF"‘1Î±) and Wnt signaling in cerebral ischemia/hypoxia-induced proliferation of neural stem cells (NSCs), we investigated the proliferation of NSCs, expression of HIF"‘1Î±, and activation of Wnt signaling under conditions of pathologic hypoxia in vitro. NSCs were isolated from 30-day-old Sprague–Dawley rats and subjected to 0.3% oxygen in a microaerophilic incubation system. Cell proliferation was evaluated by measuring the diameter of neurospheres and by bromodeoxyuridine incorporation assays. Real-time quantitative PCR and Western blotting were used to detect mRNA and protein levels of HIF-1Î±, Î²-catenin, and cyclin D1 in the NSCs. The results showed that hypoxia increased NSC proliferation and the levels of HIF-1Î±, Î²"‘catenin, and cyclin D1 (p < 0.05). Blockade of the Wnt signaling pathway decreased hypoxia-induced NSC proliferation, whereas activation of this pathway increased hypoxia-induced NSC proliferation (p < 0.05). Knockdown of HIF-1Î± with HIF-1Î± siRNA decreased Î²"‘catenin nuclear translocation and cyclin D1 expression, and inhibited proliferation of NSCs (p < 0.05). These findings indicate that pathologic hypoxia stimulates NSC proliferation by increasing expression of HIF-1Î± and activating the Wnt/Î²-catenin signaling pathway. The data suggest that Wnt/Î²-catenin signaling may play a key role in NSC proliferation under conditions of pathologic hypoxia.